2018
DOI: 10.1101/333757
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chromatin-informed inference of transcriptional programs in gynecologic and basal breast cancers

Abstract: Epigenomic data on transcription factor occupancy and chromatin accessibility can elucidate the developmental origin of cancer cells and reveal the enhancer landscape of key oncogenic transcriptional regulators. However, in many cancers, epigenomic analyses have been limited, and computational methods to infer regulatory networks in tumors typically use expression data alone, or rely on transcription factor (TF) motifs in annotated promoter regions. Here, we develop a novel machine learning strategy called PSI… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…In in vitro assay, the increased 8-mix SE-contacted gene expressions (IL-6, CCL5) from stimulated RASFs was reduced by treatment with APTO-253, a MTF1 inhibitor (figure 7C,D). [28] Furthermore, in a collagen induced arthritis (CIA) model, APTO-253 demonstrated significant preventive (online supplementary figure 8) and therapeutic activity (figure 7E,F) on arthritis formation. Collectively, these results indicated that certain TFs play critical roles in the formation of epigenomic structures induced by synergistic proinflammatory cytokines, and support MTF1 inhibition as a promising therapy candidate for RA (online supplementary figure 9).…”
Section: Transcription Factors Associated With Stimulation-induced Se Formation Control Arthritis Progressionmentioning
confidence: 98%
“…In in vitro assay, the increased 8-mix SE-contacted gene expressions (IL-6, CCL5) from stimulated RASFs was reduced by treatment with APTO-253, a MTF1 inhibitor (figure 7C,D). [28] Furthermore, in a collagen induced arthritis (CIA) model, APTO-253 demonstrated significant preventive (online supplementary figure 8) and therapeutic activity (figure 7E,F) on arthritis formation. Collectively, these results indicated that certain TFs play critical roles in the formation of epigenomic structures induced by synergistic proinflammatory cytokines, and support MTF1 inhibition as a promising therapy candidate for RA (online supplementary figure 9).…”
Section: Transcription Factors Associated With Stimulation-induced Se Formation Control Arthritis Progressionmentioning
confidence: 98%
“…In a more recent analysis, Osmanbeyoglu and colleagues evaluated the impact of the MITF transcription factor on gene expression in basal breast cancer cells. They found that MITF silencing frequently led to downregulation of pro-oncogenic factors, as c-Myc, c-Myc target genes, IL1B, NT5E (CD73) and molecules related to tumor immune evasion, as well as to consistent upregulation of genes associated with immune activation and cell adhesion, thus suggesting a tumorpromoting role for MITF activity in basal breast cancer [31]. Furthermore, as mentioned previously, the role of MITF in the regulation of the BCL2 gene activity has already been studied in melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Those interactions were curated and collected from different types of evidence such as literature curated resources, ChIP-seq peaks, TF binding site motifs, and interactions inferred directly from gene expression. The SPaRTAN framework can be extended using scATAC-seq or bulk ATAC-seq from sorted cells for more accurate representation in both promoter and enhancer regions as performed in the context of patient-specific predictive regulatory models (42)). Our model also currently rests on the assumption that a TF either induces or represses its targets, but some TFs may play either role depending on their coordination with co-factors.…”
Section: Discussionmentioning
confidence: 99%